Rancang Bangun Pengukur Suhu Tubuh Dengan Multi Sensor Untuk Mencegah Penyebaran Covid-19 - Helmy Yudhistira Putra; Utomo Budiyanto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
During the COVID-19 pandemic, the price of preventive equipment such as masks and hand sanitizers has increased significantly. Likewise, thermometers are experiencing an increase and scarcity, this tool is also sought after by many companies for screening employees and guests before entering the building to detect body temperatures that are suspected of being positive for COVID-19. The use of a thermometer operated by humans is very risky because dealing directly with people who could be ODP (People Under Monitoring/Suscpected ) or even positive for COVID-19, therefore we need tools for automatic body temperature screening and do not involve humans for the examination. This research uses the MLX-90614 body temperature sensor equipped with an ultrasonic support sensor to detect movement and measure the distance between the forehead and the temperature sensor so that the body heat measurement works optimally, and a 16x2 LCD to display the temperature measurement results. If the measured body temperature is more than 37.5 ° C degrees Celsius then the buzzer will turn on and the selenoid door lock will not open and will send a notification to the Telegram messaging application. The final result obtained is the formation of a prototype device for measuring body temperature automatically without the need to involve humans in measuring body temperature to control people who want to enter the building so as to reduce the risk of COVID-19 transmission